Telemedical prenotification of emergency departments by emergency medical services in case of severe trauma: Case report of a traffic accident Telemedizinische Voranmeldung durch den Rettungsdienst bei Schwerverletzten: Fallbericht eines Verkehrsunfalls - Eder, P. A.; Dormann, H.; Krämer, R. M.; Lödel, S. K.; Shammas, L.; Rashid, A. (Notfall und Rettungsmedizin, 2019)
Background: The collaborative treatment of severely injured trauma patients by emergency medical services (EMS) and emergency departments (ED) is a challenging task. Early and meaningful information about the medical condition prior to arriving in the ED is important for in-hospital preparation. Aim: Telemedical prenotification enables the transmission of pictures of the accident/motor vehicle crash and the medical condition to the ED. In addition to prenotification via mobile phone and the confirmation of interdisciplinary care capacities, the acute emergency management and patients’ safety can be improved by telemedical prenotification. Methods: This case report shows the advantages of telemedical prenotification examined at the hospital in Fürth (Germany). This work has been reported in line with the Surgical Case Report (SCARE) statement. Results: Telemedical prenotification has the potential to optimize in-hospital organization and improve the treatment of the patient. By receiving advanced notice, the physician on duty has enough time to study prior case files for relevant information and to initiate in-hospital preparations. The consideration of the diagnosis “prior trepanation” from the hospital database supports interpretation of CT images. Conclusion: Structured telemedical prenotification in combination with the electronic proof of interdisciplinary care capacities via standardized telecommunication interfaces extends communication possibilities between EMS and ED.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Emergency department; Emergency medical service communication systems; Patient handoff; Telemedicine; Wounds and injuries